Seven species of Labidocera (Copepoda, Calanoida, Pontellidae) from off Kenjeran, Surabaya, Indonesia - Dewi Citra Murniati; Mulyadi Mulyadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
During taxonomic studies on the pelagic copepods of the Indonesian waters, seven species of Labidocera were identified from off Kenjeran, Surabaya during 1994-2012. Four of these species, L. acuta (Dana, 1849), L. kroyeri (Brady, 1883), L. laevidentata ((Brady, 1883), and L. minuta (Giesbrecht, 1889) have been recorded previously, L. javaensis (Mulyadi, 1997) has been described as new species, and two species, L. bengalensis (Krishnaswamy, 1952) and L. sinilobata (Shen & Lee, 1963) were new records for Indonesian waters. Labidocera bengalensis and L. minuta belong to the L. minuta-group, L. kröyeri to the L. kröyeri-group, L. javaensis to the L.pectinata-group, L. sinilobata to the L. detruncata-group, while L. acuta and L. laevidentata to the unassigned-group. The number of species were highest in June 1994 and June 1998, each with 5 recorded species. The number of species were decreased, 3 species in November 2000, 1 species in October 2010 and 2 species in July 2012. Labidocera sinilobata has been found for all times sampling, L. javaensis for four times, L. acuta and L. kroyeri are found twice, and L. bengalensis L. laevidentata and L. minuta are found for one time sampling. Descriptions, measurements and figures are given for these species, along with a review of their distribution over the world’s oceans, and with taxonomic remarks, ecological notes, their species groups, and restricted synonyms.